Contract farming in developing countries: Theory, practice, and policy implications - Minot, Nicholas; Sawyer, Bradley (International Food Policy Research Institute, 2016)
Chapter 4 (Minot and Sawyer) provides clarity on the opportunities and limitations of contract farming as an institution that facilitates agricultural intensification by smallholders. They find that contract farming is more viable in value chains of fruits and vegetables for quality-sensitive markets, commercial dairy and poultry production, and certain cash crops (for example, tea, tobacco, sugarcane, and cotton). In terms of income benefits for smallholders, most case studies found considerable increases in income, in the range 25–75 percent.